2022
DOI: 10.1371/journal.ppat.1010630
|View full text |Cite
|
Sign up to set email alerts
|

Modeling recapitulates the heterogeneous outcomes of SARS-CoV-2 infection and quantifies the differences in the innate immune and CD8 T-cell responses between patients experiencing mild and severe symptoms

Abstract: SARS-CoV-2 infection results in highly heterogeneous outcomes, from cure without symptoms to acute respiratory distress and death. Empirical evidence points to the prominent roles of innate immune and CD8 T-cell responses in determining the outcomes. However, how these immune arms act in concert to elicit the outcomes remains unclear. Here, we developed a mathematical model of within-host SARS-CoV-2 infection that incorporates the essential features of the innate immune and CD8 T-cell responses. Remarkably, by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 126 publications
3
14
1
Order By: Relevance
“…However, some of the more complex models reported in the literature did give rise to interesting hypotheses that may warrant further investigation, such as the role of monocyte-to-macrophage differentiation or the role of anti-inflammatory cytokines 11 , 12 . Further, more complex models have provided complementary insight on the conditional impact of immunomodulatory treatment on disease severity that are consistent with the results reported herein 61 , 62 .…”
Section: Discussionsupporting
confidence: 86%
“…However, some of the more complex models reported in the literature did give rise to interesting hypotheses that may warrant further investigation, such as the role of monocyte-to-macrophage differentiation or the role of anti-inflammatory cytokines 11 , 12 . Further, more complex models have provided complementary insight on the conditional impact of immunomodulatory treatment on disease severity that are consistent with the results reported herein 61 , 62 .…”
Section: Discussionsupporting
confidence: 86%
“…Attempts to quantify the inter-individual variability in SARS-CoV-2 infection dynamics have been made in studies using various models and data ( Goyal et al, 2020 , Chatterjee et al, 2022 , NĂ©ant, et al, 2021 , Gonçalves, 2020 ). These quantitative models have been used to predict the efficacy of antiviral treatment and to investigate the factors affecting individual differences in outcomes in clinical trials as we did in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, we considered only that administration of an entry inhibitor inhibits de novo viral infection of uninfected cells. A mathematical modeling study suggested that there is a large difference in the sensitivity of immune responses related to CD8T cell exhaustion due to viral infection between patients with mild and severe cases ( Chatterjee et al, 2022 ). If suppression of viral load with antiviral treatment restores such immune cell activity and leads to a greater rate of elimination of infected cells, viral load may be greatly reduced as our previous mathematical modeling study have shown ( Kim, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the changes in the preference of the Omicron variant for different entry routes may help evaluate the efficacies of entry inhibitors in clinical development and optimise entry inhibitor-based treatments (Gunst et al, 2021; Zhuravel et al, 2021). Mathematical models of SARS-CoV-2 kinetics have provided valuable insights into COVID-19 disease progression, drug action, and the effectiveness of vaccines and treatments (Amidei and Dobrovolny, 2022; Chatterjee et al, 2022; Desikan et al, 2021; Garg et al, 2021; Gonçalves et al, 2020; Goyal et al, 2020; Ke et al, 2021; Kissler et al, 2021; NĂ©ant et al, 2021; Padmanabhan et al, 2022; Perelson and Ke, 2020). Here, adapting a previously developed mathematical model of SARS-CoV-2 entry (Padmanabhan et al, 2020) to the analysis of in vitro data on variants (Garcia-Beltran et al, 2021; Hoffmann and et al, 2021), we quantified the altered usage of host proteases required for entry by the Omicron variant relative to the original strain and the Delta variant.…”
Section: Discussionmentioning
confidence: 99%